Pojetí historie v českém katolickém exilu - Hanuš, Jiří; Husák, Petr (Lidé města, 2019)
History belongs among the traditional “Czech national topics”, especially in relation to the characteristics of national emancipation and of the formation of a Czech national identity in the 19 th century. History also belongs among the great topics of the Catholic subculture, through which we can observe different authors with various interpretations of (Czech) history. The authors of the paper focus on the 20th century production of the Catholic historical exile, especially on its two main waves, i.e. after 1948 and after 1968. In addition to the political and the social changes, the influence of the Second Vatican Council (1962–1965) proved to be significant in the interpretation of events. The paper is designed so that examples of Catholic approaches to history are described from the perspective of literary genres (the lives of the saints, spiritual literature, theology of history, historical synthesis, poetry, “fragments”), to which individual figures are assigned. The final summary attempts to define the specifics of Catholic exile publications.